Comprehensive evaluation of critical-size calvarial defect in athymic rat model - Parco, Todd M.; Wagner, Jon D.; Parbhoo, Pratish; Soviak, Caroline; Hu, Yuan; Araiza, John T.; O'Beirne, Colin; Javaid, Sehrish; Parachuru, Praveen; Lewis, Matthew; Acosta, Carlos A.; Settem, Rajendra Prasad; et al. (Frontiers in Physiology, 2025)
The critical size defect (CSD), which defines the threshold beyond which spontaneous healing fails, serves as a foundational tool in bone regeneration research. This study investigated calvarial CSDs in an athymic rat model to refine the definition, emphasize its significance, and address inconsistencies in experimental design across existing information. A 4.5 mm diameter calvarial defect was surgically created in athymic rats. Bone regeneration was assessed using micro-computed tomography (micro-CT) at 1, 4, and 8 weeks after the surgery, compared to the baseline (day 0) post-surgery. Histological assessment was performed using a standard hematoxylin and eosin (H&E) staining protocol at 8 weeks post-surgery. Quantitative data from micro-CT analysis revealed no increase in bone volume or percentage volume from day 0 to week 1. We observed bone regeneration initiated at week 4 and progressed through week 8, with healing percentages ranging from 0.1% to a maximum of 7%. Histological examination of tissue at week 8 revealed the presence of loose collagen fibers and interspersed fibroblasts, with no mineralization as observed. These findings confirm that the 4.5 mm defect in calvarial bone qualifies as a critical-size defect in the athymic rat model. The study enhances our understanding of bone healing dynamics in CSDs and provides a validated platform for evaluating novel regenerative therapies.